¿Cuál es la relevancia de los reflejos primitivos en bebés de 0 a 6 meses, para la consulta en optometría? (2022)
Psychomotor development in children relies on an adequate and prompt environmental stimulation. Moreover, correct brain development and maturation are also dependent of external stimuli as they generate neural connection which are crucial for the total integration of psychomotor evolution.